In Memoriam of Professor Stanisław Pabis - Jaros, Małgorzata; Markowski, Marek; Myhan, Ryszard (Technical Sciences, 2020)
Professor Stanisław Pabis passed away suddenly on September 13, 2019, at the age of 94. We lost an outstanding scientist in the field of Biosystems Engineering who founded the scientific school of methodology of empirical sciences and who made a significant contribution to the development of systems engineering in agriculture and food processing.